Electroacupuncture Attenuates Inflammation after Ischemic Stroke by Inhibiting NF-κB-Mediated Activation of Microglia. (19th August 2020) - Liu, Rong; Xu, Neng-Gui; Yi, Wei; Ji, Chang
Abstract : Microglial activation and microglia-mediated inflammation play an important role in the occurrence, development, and outcome of stroke. Brain injury induces the activation and release of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF- α ), interleukin- (IL-) 1 β, and IL-6. Many studies have confirmed that acupuncture is effective in treating ischemic stroke. However, its protective mechanism against ischemic brain injury is complex and multifactorial. In this study, we observed the effects of electroacupuncture at Baihui (GV20) and Dazhui (GV14) on microglial activation and inflammation in the cortical ischemic penumbra (IP) of permanent middle cerebral artery occlusion (pMCAO) rats. It was found that electroacupuncture inhibited the degeneration and necrosis of microglia in the cortical IP and ameliorated mitochondrial damage. Immunofluorescence and western blot analysis showed that microglia were in a resting state or weakly activated in the normal brain. After cerebral ischemia, the expression of microglial markers (Iba-1 and CD11b) increased, and NF- κ B p65, IL-1 β, and TNF- α expression gradually increased. The dynamic changes were generally temporally consistent. Electroacupuncture downregulated the expressions of Iba-1 and CD11b. Additionally, it inhibited the expression of NF- κ B p65, IL-1 β, and TNF- α and reduced the conversion of microglia to the M1 phenotype after ischemia. Electroacupuncture regulated the activation of microglia and microglia-mediated inflammation after cerebral ischemia, confirming the relevant theories regarding the effect of acupuncture treatment on cerebral ischemia and guiding clinical practice.